2011
DOI: 10.5152/eajm.2011.07
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Amlodipine on the Biochemical and Histopathological Changes in the Rabbit Ileum Subjected to Ischemia-Reperfusion

Abstract: Objective: The aim of this study was to determine the potential, protective effects of amlodipine in an experimental, ischemia-reperfusion (I/R) model in the rabbit small intestine. Materials and Methods:The rabbits were divided into four groups: sham-operated, amlodipine (10 mg/kg) + sham-operated, I/R, and I/R + amlodipine (10 mg/kg) groups. An intestinal I/R model was applied to the rabbits. The superior mesenteric artery was occluded for 1 h with an atraumatic vascular clamp and then was reperfused for 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…24,25 Coskun et al demonstrated that AML treatment decreased MDA levels. 41 In the present study, MDA levels were increased in the P-induced toxicity groups, and the treatment with AML significantly reduced these levels.…”
Section: Groupsupporting
confidence: 54%
“…24,25 Coskun et al demonstrated that AML treatment decreased MDA levels. 41 In the present study, MDA levels were increased in the P-induced toxicity groups, and the treatment with AML significantly reduced these levels.…”
Section: Groupsupporting
confidence: 54%
“…Following ischemia lead to severe injury not only in ovaries but also in the different tissues 36,37 . It was demonstrated that antioxidant activity is important for repair of tissue damage 38 .…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…Coskun et al . () examined the effects of AML and concluded that GSH levels significantly increased in the intestinal I/R in rats.…”
Section: Discussionmentioning
confidence: 99%